Impact of Dividend Policy on Performance of Firms Having Stocks Listed In an Emerging Stock Market - Rehman, Mobeen Ur; Hussain, Aabid (Asian Journal of Empirical Research, 2013)
In this research paper we have discussed various theories regarding the impact of dividend policy on the performance of the firms. We have also analyzed these theories in the light of the companies that are practically undergoing through the debate of determining the key factors, which play a crucial role in measuring the performance of the companies. There can not only be a single determinant having impact on the overall financial performance of the firm rather there can be number of dividends that can have a combined effect of the overall performance. In this paper we have tried to find out the key indicators that do impact the performance of the firm and are also incorporated in the dividend policy of the firm. The impact can either be positive or negative depending upon the nature of variable. In this paper we have taken sample of 475 companies and the data is the secondary one. Ratios have been computed of all the companies that basically determine the dividend policy and then the correlation tests have been run to see the whether the results are significant or not. In the conclusion we have mentioned the variables that play a key role in determining the performance of the firms.